Algebra


  1. If
    x
    =
    y
    =
    z
    and x + y + z ≠ 0, then each ratio is
    xa + yb + zcya + zb + xcza + xb + yc










  1. View Hint View Answer Discuss in Forum

    x
    =
    y
    =
    z
    xa + yb + zcya + zb + xcza + xb + yc

    =
    x + y + z
    xa + yb + zc + ya + zb + xc + za + xb + yc

    =
    x + y + z
    xa + ya + za + yb + ya + yc + zc + zb + zc + za

    =
    x + y + z
    a(x + y + z) + b(x + y + z) + c (x + y + z)

    =
    x + y + z
    (a + b + c)(x + y + z)

    =
    1
    a + b + c

    Correct Option: D

    x
    =
    y
    =
    z
    xa + yb + zcya + zb + xcza + xb + yc

    =
    x + y + z
    xa + yb + zc + ya + zb + xc + za + xb + yc

    =
    x + y + z
    xa + ya + za + yb + ya + yc + zc + zb + zc + za

    =
    x + y + z
    a(x + y + z) + b(x + y + z) + c (x + y + z)

    =
    x + y + z
    (a + b + c)(x + y + z)

    =
    1
    a + b + c


  1. If x : y = 3 : 2, then the value of
    x + y
    is
    x - y










  1. View Hint View Answer Discuss in Forum

    x
    +
    3
    y2

    By componendo and dividend,
    x + y
    =
    3 + 2
    x - y3 - 2

    x + y
    =
    5
    5 : 1
    x - y1

    Correct Option: A

    x
    +
    3
    y2

    By componendo and dividend,
    x + y
    =
    3 + 2
    x - y3 - 2

    x + y
    =
    5
    5 : 1
    x - y1



  1. If a² + b² + c² – ab – bc – ca = 0, Then a : b : c is :









  1. View Hint View Answer Discuss in Forum

    a² + b² + c² – ab – bc – ca = 0
    ⇒ 2a² + 2b² + 2c² – 2ab – 2bc – 2ca = 0
    ⇒ (a² + b² – 2ab) + (b² + c² – 2bc) + (c² + a² – 2ca) = 0
    ⇒ (a – b)2 + (b – c)2 + (c – a)2 = 0
    [If x² + y² + z² = 0 then, x = 0, y = 0, z = 0]
    ∴ a – b = 0 ⇒ a = b
    b – c = 0 ⇒ b = c
    c – a = 0 ⇒ c = a
    ∴ a = b = c
    ∴ a : b : c = 1 : 1 : 1

    Correct Option: B

    a² + b² + c² – ab – bc – ca = 0
    ⇒ 2a² + 2b² + 2c² – 2ab – 2bc – 2ca = 0
    ⇒ (a² + b² – 2ab) + (b² + c² – 2bc) + (c² + a² – 2ca) = 0
    ⇒ (a – b)2 + (b – c)2 + (c – a)2 = 0
    [If x² + y² + z² = 0 then, x = 0, y = 0, z = 0]
    ∴ a – b = 0 ⇒ a = b
    b – c = 0 ⇒ b = c
    c – a = 0 ⇒ c = a
    ∴ a = b = c
    ∴ a : b : c = 1 : 1 : 1


  1. If a² + 13b² + c² – 4ab – 6bc = 0, then a : b : c is









  1. View Hint View Answer Discuss in Forum

    a² + 13b² + c² – 4ab – 6bc = 0
    ⇒ a² – 4ab + 4b² + 9b² + c² – 6bc = 0
    ⇒ a² – 4ab + 4b² + c² – 6bc + 9b² = 0
    ⇒ (a – 2b)² + (c – 3b)² = 0
    ⇒ a – 2b = 0 and c – 3b = 0
    ⇒ a = 2b and c = 3b

    a
    =
    2
    and
    b
    =
    1
    b1c3

    ∴ a : b : c = 2 : 1 : 3

    Correct Option: C

    a² + 13b² + c² – 4ab – 6bc = 0
    ⇒ a² – 4ab + 4b² + 9b² + c² – 6bc = 0
    ⇒ a² – 4ab + 4b² + c² – 6bc + 9b² = 0
    ⇒ (a – 2b)² + (c – 3b)² = 0
    ⇒ a – 2b = 0 and c – 3b = 0
    ⇒ a = 2b and c = 3b

    a
    =
    2
    and
    b
    =
    1
    b1c3

    ∴ a : b : c = 2 : 1 : 3



  1. If (2x – y)² + (3y – 2z)² = 0, then the ratio x : y : z is :









  1. View Hint View Answer Discuss in Forum

    If a² + b² = 0
    ⇒ a = 0 and b = 0
    ∴ (2x – y)² + (3y – 2z)² = 0
    ∴ 2x – y = 0 ⇒ 2x = y
    ⇒ x : y = 1 : 2 and, 3y – 2z = 0
    ⇒ 3y = 2z
    ⇒ y : z = 2 : 3
    ∴ x : y : z = 1 : 2 : 3

    Correct Option: B

    If a² + b² = 0
    ⇒ a = 0 and b = 0
    ∴ (2x – y)² + (3y – 2z)² = 0
    ∴ 2x – y = 0 ⇒ 2x = y
    ⇒ x : y = 1 : 2 and, 3y – 2z = 0
    ⇒ 3y = 2z
    ⇒ y : z = 2 : 3
    ∴ x : y : z = 1 : 2 : 3